Convergent innovation for sustainable economic growth and affordable universal health care: Innovating the way we innovate - Dubé, Laurette; Jha, Srivardhini K.; Faber, Aida; Struben, Jeroen; London, Ted; Mohapatra, Archisman; Drager, Nick; Lannon, Chris; Joshi, Pramod Kumar; McDermott, John (Wiley, 2014)
This paper introduces convergent innovation (CI) as a form ofmeta‐innovation—an innovation in the way we innovate. CI integrates human and economic development outcomes, through behavioral and ecosystem transformation at scale, for sustainable prosperity and affordable universal health care within a whole‐of‐society paradigm. To this end, CI combines technological and social innovation (including organizational, social process, financial, and institutional), with a special focus on the most underserved populations. CI takes a modular approach that convenes around roadmaps for real world change—a portfolio of loosely coupled complementary partners from the business community, civil society, and the public sector. Roadmaps serve as collaborative platforms for focused, achievable, and time‐bound projects to provide scalable, sustainable, and resilient solutions to complex challenges, with benefits both to participating partners and to society. In this paper, we first briefly review the literature on technological innovation that sets the foundations of CI and motivates its feasibility. We then describe CI, its building blocks, and enabling conditions for deployment and scaling up, illustrating its operational forms through examples of existing CI‐sensitive innovation.